The influence of Economic Value Added (EVA), Return On Investment (ROI ), and Company Size Against Company Value - Indahwati, Vanessa; Hizazi, Achmad; Mansur, Fitrini (Faculty of Economics and Business Universitas Jambi, 2023)
This study is entitled the influence of economic value added (EVA), return on investment (ROI), and company size on company value. The case study of this research is on basic and chemical industry sector companies on the Indonesia Stock Exchange in 2016-2017. The sample in this study was 56 basic and chemical industry companies listed on the Indonesia Stock Exchange in 2016-2017. The data analysis method used multiple linear regression analysis. The results of this study indicate that economic value added (EVA), return on investment (ROI), and company size simultaneously affect company value. economic value added (EVA) partially has a positive effect on company value, return on investment (ROI) partially has a positive effect on company value and company size partially has a positive effect on company value in basic and chemical industry companies listed on the Indonesia Stock Exchange